Telaah Kritis Putusan MK Terkait Persetujuan Tertulis dari Presiden dalam Pemeriksaan Anggota DPR yang Diduga Melakukan Tindak Pidana - Pradana, Hasyimi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the judges' considerations in the Constitutional Court Decision Number 16/PUU-XVI/2018 regarding the provisions of Article 245 paragraph (1) of Law Number 2 of 2018, and to analyze the legal consequences of the Constitutional Court Decision Number 16/PUU-XVI/2018 regarding written approval of the President in the examination of members of the House of Representatives suspected of committing a crime. This study used a normative juridical method with a statutory approach. The data sources (the primary and secondary legal materials) were analyzed descriptively qualitatively. The study results showed two judges' considerations regarding the provisions of Article 245 paragraph (1) of Law Number 2 of 2018. First, it was contrary to the principle of equality in law and government. Second, the assumption that the Honorary Court of the Council was an ethical institution with no direct relationship with the criminal justice system. The legal consequences of the Constitutional Court's Decision Number 16/PUU-XVI/2018 regarding the written approval of the President in the examination of members of the House of Representatives were causing legal uncertainty, legal injustice, and abuse of authority that could trigger a politics of retaliation.